Development of Herpetoculture in Costa Rica: Current Situation of Herpetariums and Ex Situ Management of Reptiles and Amphibians - Arias-Ortega, Jazmín (2016)
The maintenance of reptiles and amphibians in captivity has greatly developed worldwide, becoming the basis of many conservation, education, and research programs. In Costa Rica, this trend is evident in the proliferation of centers that maintain herpetofauna in the last two decades.  Despite this development, there is no information available on the centers existing in Costa Rica, and the way they operate, or the potential impacts they could have on the species kept remain unknown. In this study, we describe the facilities currently operating in the country, through a series of interviews to their owners or technical staff, and in situ observations.  A total of 33 centers were found, which keep up to 144 species of reptiles and amphibians. This large number of facilities resulted from the development of the tourism industry in the country: most of them are intended to display animals, although some reported educational purposes. Most interviewed staff claims that generation of knowledge is one of the main objectives of their center. However, only four of them showed clear evidence of research programs. A significant percentage of centers get their animals directly from the natural environment, a practice that might have an impact on species with reduced populations in the wild. This seems to be the case of the Bushmaster Lachesis stenophrys, found in 66% of the centers, despite being a species that is nowadays threatened in the country.  The existence of these facilities demonstrates the interest Costa Rica society has on wildlife, and it is an interesting mosaic of experiences, opportunities, and challenges for the environmental scene of the country.